SHM_116708_HST_3D The Aranäs Helmet - Eriksson, Thomas; National Historical Museums (National Historical Museums, 2026)
Structured light 3D model of the Aranäs Helmet, a 'great helm' style helmet made of iron around 1300 CE during the Swedish Middle Ages. Collected from Årnas in Västergötland, it is currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=408

Link to Sök I Samlingarna

https://samlingar.shm.se/object/5A6E6CF8-22F3-4609-A5E6-AC9DABD5B8E6
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Dynamic Collections; Årnas; Swedish Middle Ages; 3D Model; Museum Object; Structured Light Scanning; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi